Tren, Research Gap, dan Arah Pengembangan Penelitian Integrasi Nilai Spiritual dalam Pendidikan di Indonesia: Sebuah Systematic Literature Review - Atika Maulidina Hs; Agung Setyawan; Tyasmiarni Citrawati; Heri Miarto (STKIP AL HIKMAH SURABAYA, 2026)
Research on the integration of spiritual values in Indonesian education has grown considerably; however, its research trends, development patterns, and existing gaps have not been comprehensively synthesized. This study aims to synthesize empirical findings, map research trends, identify research gaps, and propose future research directions concerning the integration of spiritual values in Indonesian education. A Systematic Literature Review following the PRISMA guidelines was employed. The reviewed articles were collected from SINTA-indexed national journals published within the last five years. From approximately 1,000 initially identified articles, 19 studies met the inclusion criteria and were analyzed using descriptive and thematic approaches. The findings reveal that existing studies are predominantly qualitative and focus on primary education, emphasizing religious habituation, teacher role modeling, school culture, and the integration of spiritual values into Islamic Religious Education and Science learning. Most studies remain at the descriptive–exploratory and interpretative–reflective stages, while experimental research, instructional model development, digital technology integration, AI, and spiritual reasoning remain largely unexplored. These findings indicate the need for more transformative research that integrates spiritual values with digital pedagogy, AI, and ethical dimensions of learning. This review provides a comprehensive overview of current research and offers a foundation for future research agendas on spiritual value integration in Indonesian education.